1999
DOI: 10.1016/s0168-6445(99)00008-x
|View full text |Cite
|
Sign up to set email alerts
|

3′-End processing of pre-mRNA in eukaryotes

Abstract: Abstract3P-Ends of almost all eukaryotic mRNAs are generated by endonucleolytic cleavage and addition of a poly(A) tail. In mammalian cells, the reaction depends on the sequence AAUAAA upstream of the cleavage site, a degenerate GU-rich sequence element downstream of the cleavage site and stimulatory sequences upstream of AAUAAA. Six factors have been identified that carry out the two reactions. With a single exception, they have been purified to homogeneity and cDNAs for 11 subunits have been cloned. Some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
237
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(239 citation statements)
references
References 110 publications
(193 reference statements)
2
237
0
Order By: Relevance
“…However, it is not surprising that increased gene expression occurs with enhanced mRNA processing, since proteins that catalyze polyadenylation are associated with RNA polymerase II (Pol II), providing a link between transcription and formation of the 3 0 end of mRNA (Maniatis and Reed, 2000;Proudfoot et al, 2000). A functional polyadenylation signal terminates transcription and release Pol II (Whale and Ruegsegger, 1999;Shatkin and Manley, 2000), although polyadenylation seems to continue post-transcriptionally (Osheim et al, 1999(Osheim et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not surprising that increased gene expression occurs with enhanced mRNA processing, since proteins that catalyze polyadenylation are associated with RNA polymerase II (Pol II), providing a link between transcription and formation of the 3 0 end of mRNA (Maniatis and Reed, 2000;Proudfoot et al, 2000). A functional polyadenylation signal terminates transcription and release Pol II (Whale and Ruegsegger, 1999;Shatkin and Manley, 2000), although polyadenylation seems to continue post-transcriptionally (Osheim et al, 1999(Osheim et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The DSE is less conserved and more diffuse than the PAS [2,19]. The presence of this element was suggested by the observation that a deletion more than 10 nucleotides downstream of the cleavage site reduced polyadenylation three-fold [42].…”
Section: The Downstream Element (Dse)-mentioning
confidence: 99%
“…Mutation of the PE forces cleavage to occur at unspecific locations in the 3′ untranslated region [19].…”
Section: Sequence Elements In Yeastmentioning
confidence: 99%
“…The 39 untranslated region (39 UTR) of an mRNA plays an important role in 39 end processing of eukaryotic transcripts+ Sequence motifs, located in the 39 UTR, are necessary for cleavage at a specific site and the addition of a poly(A) tail (for reviews, see Wahle & Rüegsegger, 1999;Zhao et al+, 1999)+ The sequence motifs of yeast transcripts that direct cleavage and polyadenylation are not as conserved as in higher eukaryotes+ Several yeast 39 untranslated regions were shown to carry degenerate motifs that can at least partially replace one another (Egli et al+, 1995;Guo et al+, 1995)+ Deletion of the 39 UTR usually results in a significant reduction of the amount of gene product+ A deletion of the 39 UTR of the TRP4 gene led to a reduced amount of gene product without affecting cellular growth rates (Düvel et al+, 1999)+ A large multiprotein complex performs cleavage and polyadenylation of pre-mRNAs in eukaryotes (Keller & Minvielle-Sebastia, 1997;Zhao et al+, 1999)+ A subset of these factors affects only the polyadenylation efficiency whereas others are necessary for both cleavage and polyadenylation+ A complex pattern of interactions connects the different components with each other and cooperative interactions between the processing factors have been observed (Kessler et al+, 1997)+ As a consequence, cleavage and polyadenylation are coupled processes in vivo+ However, an uncoupling of cleavage and polyadenylation was achieved in vivo in yeast by using an artificial hammerhead ribozyme as a mRNA 39 end processing signal (Egli & Braus, 1994)+ Ribozymes are RNAs with an enzymatic activity for RNA cleavage (Altman, 1990;Cech, 1990)+ Hammerhead ribozymes are a subset of self-cleaving ribozymes that were originally isolated from plant viroids (Symons, 1992)+ Hammerhead ribozymes consist of three stem-loop-forming regions and two highly conserved single-stranded sequences+ Cleavage occurs at a triplet sequence, usually GUC+ Hydrolysis of the phosphodiester bond results in a 29-39-cyclic phosphate and a 59-hydroxyl product (Tanner, 1999)+ This is in contrast to enzymatic cleavage by processing factors that generally result in a 39-hydroxyl and a 59-phosphate+ Because the catalytic action of ribozymes has been studied thoroughly, new ribozymes were constructed providing applications in biotechnology and medicine+ Trans-acting ribozymes, for example, cleave target mRNAs at specific cleavage motifs, and are widely used to decrease the amount of the mRNA of genes of interest (Birikh et al+, 1997;Tanner, 1999)+ The hammerhead ribozyme used in this study cleaves itself efficiently in yeast (Egli & Braus, 1994)+ This prompted us to determine whether a hammerhead ribozyme could replace the normal mechanism of 39 end formation in an authentic yeast transcript+ We have now found that replacing the 39 UTR of the TRP4 gene with a hammerhead ribozyme results in a ...…”
Section: Introductionmentioning
confidence: 99%